Profile of Creative Thinking Skills and Analysis of Students' Perceptions of Physics Learning - Elvira Clarita Melur; Winny Liliawati; Achmad Samsudin; Lina Aviyanti; Andy Setiawan (Postgraduate, University of Mataram, 2025)
This study aims to describe the profile of students' creative thinking skills in Physics and analyze their perceptions of Physics learning. The method used is descriptive quantitative involving 59 high school students selected through random sampling techniques. The instruments used include creative thinking skills tests and student response questionnaires that are analyzed using descriptive statistics. The results of the study indicate that in general students' creative thinking skills are in the moderate category with an analysis per aspect, where